Analysis Of Clerodendrum inerme Plant Compounds as Anti Diabetes Mellitus Through Network Pharmacology Approach - Jamil, Ahmad Shobrun; Hilmy, Fauzan (Journal of Biomedicine and Translational Research, 2023)
Background:  Diabetes mellitus prevalence in Indonesia has surged. In 2021, an estimated 19.5 million people had diabetes, with a 10.6% age-adjusted prevalence. Projections indicate around 9.5 million cases by 2024. Diabetes medications, such as metformin, are commonly used, although these medications have adverse effects. A common choice for chronic diseases like DM is the use of natural medications. A plant known as Clerodendrum inerme has the potential to alleviate diabetes, but little is known about its molecular mechanismsObjective: The purpose of this study was to explore the content of Clerodendrum inerme plant compounds and their potential for cases of Diabetes Mellitus.Methods: The KNApSAcK was used to conduct an analysis of plant parts of Clerodendrum inerme to seek out chemicals present in plants. A screening was done to find compounds by estimating Absorption, Distribution, Metabolism, and Excretion (ADME) parameters using the canonical Simplified molecular-input line-entry system (SMILES) on the SwissADME. On the SwissTargetPrediction tool, predictions of target proteins from compounds that pass screening are connected to various probable proteins. utilising the String-db  to show the network between target proteins and associated diseasesResults: The Clerodendrum inerme consist of 24 different compound. The 24 compounds were screened, and the results showed that 4 of them, specifically (Z)-3-Hexenyl beta-D-glucopyranoside, Rhodioloside, Sammangaoside B, and Clerodermic acid, had the potential to be developed into therapeutic agent. The compound are then analysed in order to find the protein target associated with diabetes mellitus and predict its networks. The findings indicate that multiple target proteins, including GSK3B, PPARG, DPP4, and STAT3, are connected to diabetes mellitus.Conclusion: It has been shown that (Z)-3-Hexenyl beta-D-glucopyranoside, or clerodermic acid, is able to attach to the proteins GSK3B, PPARG, DPP4, and STAT3, which are all linked to diabetes mellitus.